Effect of Mahjong on children's intelligence quotient - Higashijima, Takefumi; Akimoto, Taisuke; Sakata, Katsumi (Frontiers in Psychology, 2022)
This study investigated the effect of Mahjong, which is a table game played by three or four players and involves intellectual activity, on the intelligence quotient (IQ) in children. The participants were children between the ages of 6 and 15 years, and their IQ was assessed immediately after enrolling in children's Mahjong classes, and one year after the enrollment using the Wechsler Intelligence Scale for Children Fourth Edition (WISC Ⅳ). Twenty children were included in the analysis. Their mean age at the time of the initial examination was 9 years and 6 months. In addition, we conducted a one-year post-examination. The change in IQ for this group was compared to that of a historical control group with a similar age range and test-retest interval. The mean overall full-scale IQ of the 20 children during the initial and post-one-year examinations was 106.05 and 113.75, respectively, and showed a statistically significant increase (p<0.01). Based on the subscale index, the verbal comprehension (VCI) and processing speed index (PSI) scores both showed a statistically significant increase from 100.6 to 106.75 and 108.05 to 119.05 (p<0.01), respectively. PSI of the children included in the analysis showed a statistically significant increase compared to the historical control group. This study suggests that children who participate in Mahjong classes during their childhood have increased PSI scores of WISC-Ⅳ.